1990
DOI: 10.1007/bf01537244
|View full text |Cite
|
Sign up to set email alerts
|

Gastric dysrhythmias and nausea of pregnancy

Abstract: Gastric dysrhythmias have been recorded from patients with a variety of nausea syndromes. The aim of this study was to measure gastric myoelectric activity in women with and without nausea during the first trimester of pregnancy. In 32 pregnant women gastric myoeletric activity was recorded for 30-45 min with cutaneous electrodes that yielded electrogastrograms (EGGs). Frequencies of the EGG waves were analyzed visually and by computer. Subjects rated their nausea at the time of EGG recording on a visual analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(73 citation statements)
references
References 20 publications
3
69
0
1
Order By: Relevance
“…Gastric dysrhythmia has been observed in a number of clinical settings [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12]and is known to be associated with gastric motility disorders [13]. It plays an important pathophysiological role in at least a subgroup of patients with gastroparesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric dysrhythmia has been observed in a number of clinical settings [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12]and is known to be associated with gastric motility disorders [13]. It plays an important pathophysiological role in at least a subgroup of patients with gastroparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric dysrhythmia is used to describe the abnormal rhythmicity of the gastric slow waves and is classified into tachygastria, bradygastria and arrhythmia [1]. Gastric dysrhythmia has been observed in a variety of clinical studies [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13], including patients with unexplained nausea and vomiting [2, 3], gastroparesis [4, 5], type-II diabetes [6], early pregnancy [7, 8], gastroesophageal reflux disease [9], vagotomy [10], after surgery [11]and after bone marrow or stem cell transplantation [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously suggested a possible association between nausea and gastric dysrhythmia [13, 14, 15, 16]. Regularization of the slow-wave frequency has been proposed as a possible explanation for the improvement in symptoms [12].…”
Section: Discussionmentioning
confidence: 99%
“…Myoelectrical abnormalities of the stomach have been recorded in patients with unexplained nausea and vomiting, during pregnancy or motion, and in patients with anorexia nervosa, and dysrhythmia seems to correlate with antral hypomotility and delayed gastric emptying. [9][10][11][12] Neonatal motility studies (in both preterm and term infants) have demonstrated impaired gastrointestinal motility, characterized by the presence of motor quiescence alternating with episodes of nonmigrating phasic activity without clear migrating Background. To evaluate the effect of feeding with milk on the gastrointestinal tract, we studied gastric electrical activity in 27 healthy fullterm newborns (15 formula-fed newborns and 12 breast-fed newborns) during the first 6 months of life.…”
Section: Introductionmentioning
confidence: 99%